Research on the Influence of Dynamic Work Environment on Employees’ Innovative Performance in the Post-epidemic Era – The Role of Job Crafting and Voice Behavior - Wang, Jianhua (Frontiers in Psychology, 2021)
In today's interconnected world, environmental uncertainty is higher than ever. Under the new economic normal, innovation-driven has become the key to the transformation and upgrading of various enterprises. Employees’ behavior affects the company's innovative performance, but it is also deeply affected by the dynamic work environment. The sudden epidemic has greatly increased the environmental dynamics and uncertainties faced by individuals, and also caused many changes in individual behavior. However, the research on the mediating mechanism and boundary conditions of how the dynamic work environment affects employee behavior and results is relatively few. Based on uncertainty reduction theory and innovative performance theory, and following the research paradigm of "environment-behavior-performance", a moderated mediation model with job crafting as the mediating variable and voice behavior as the moderating variable is constructed. Through the statistical analysis of 210 valid questionnaires for employees in different types of enterprises, the mechanism of how the dynamic work environment affects innovative performance by promoting employees to carry out job crafting is discussed. According to the test results, the dynamic work environment has a significant positive impact on individual innovative performance, and job crafting plays a mediating role in the relationship between the two. In addition, voice behavior positively moderate the relationship between dynamic work environment and job crafting, and the indirect relationship between dynamic work environment and innovative performance through job crafting.